A paradigmatic change: Linking fullerenes to electron acceptors - Feng, Lai; Rudolf, Marc; Wolfrum, Silke; Troeger, Anna; Slanina, Zdenek; Akasaka, Takeshi; Nagase, Shigeru; Martin, Nazario; Ameri, Tayebeh; Brabec, Christoph; Guldi, Dirk Michael (Journal of the American Chemical Society, 2012)
The potential of Lu N@C and its analogues as electron acceptors in the areas of photovoltaics and artificial photosynthesis is tremendous. To this date, their electron-donating properties have never been explored, despite the facile oxidations that they reveal when compared to those of C . Herein, we report on the synthesis and physicochemical studies of a covalently linked Lu N@C -perylenebisimide (PDI) conjugate, in which PDI acts as the light harvester and the electron acceptor. Most important is the unambiguous evidence-in terms of spectroscopy and kinetics-that corroborates a photoinduced electron transfer evolving from the ground state of Lu N@C to the singlet excited state of PDI. In stark contrast, the photoreactivity of a C -PDI conjugate is exclusively governed by a cascade of energy-transfer processes. Also, the electron-donating property of the Lu N@C moiety was confirmed through constructing and testing a bilayer heterojunction solar cell device with a PDI and Lu N@C derivative as electron acceptor and electron donor, respectively. In particular, a positive photovoltage of 0.46 V and a negative short circuit current density of 0.38 mA are observed with PDI/Ca as anode and ITO/Lu N@C as cathode. Although the devices were not optimized, the sign of the V and the flow direction of J clearly underline the unique oxidative role of Lu N@C within electron donor-acceptor conjugates toward the construction of novel optoelectronic devices. © 2012 American Chemical Society.

Charge carrier dynamics in a ternary bulk heterojunction system consisting of P3HT, fullerene, and a low bandgap polymer - Koppe, Markus; Egelhaaf, Hans-Joachim; Clodic, Ewan; Morana, Mauro; Lueer, Larry; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Ameri, Tayebeh; Brabec, Christoph (Advanced Energy Materials, 2013)
The photoresponse of P3HT:PC BM based organic solar cells can be enhanced by blending the bulk heterojunction with the low band gap polymer Si-PCPDTBT. Organic solar cells containing the resulting ternary blend as the photoactive layer deliver short circuit currents of up to 15.5 mA cm. Morphological studies show modest phase separation without the perturbation of the crystallinity of the P3HT:PC BM matrix, in accordance with the measured acceptable fill factors. Picosecond time-resolved pump-probe spectroscopy reveals that the sensitization of P3HT:PC BM with Si-PCPDTBT involves the transfer of photogenerated positive polarons from the low band gap polymer to P3HT within few hundreds of picoseconds. Intensity dependent experiments in combination with global fitting show that the charge transfer from Si-PCPDTBT to P3HT competes with non-geminate charge carrier recombination of the holes in the Si-PCPDTBT phase with electrons in the PC BM phase, both processes being of diffusive nature. At excitation densities corresponding to steady state conditions under one sun, modelling predicts hole transfer efficiencies exceeding 90%, in accordance with IQE measurements. At higher pump intensities, bimolecular recombination suppresses the hole transfer process effectively. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Electrostatic layer-by-layer construction and characterization of photoelectrochemical solar cells based on water soluble polythiophenes and carbon nanotubes - Sgobba, Vito; Troeger, Anna; Cagnoli, Rita; Mateo-Alonso, Aurelio; Prato, Maurizio; Parenti, Francesca; Mucci, Adele; Schenetti, Luisa; Guldi, Dirk Michael (Journal of Materials Chemistry, 2009)
Positively and negatively charged functionalized polythiophenes and single walled carbon nanotubes were sequentially adsorbed on indium tin oxide electrodes by electrostatic and van der Waals interactions using the layer-by-layer deposition method. The resulting donor/acceptor photoelectrodes were tested as photoelectrochemical cells. Upon illumination, monochromatic incident photoconversion efficiencies of 8.2 and 4.3% were determined for eight stacks of single walled carbon nanotubes with ammonium and sulfonate polythiophene derivatives, respectively. © The Royal Society of Chemistry 2009.

Improving photocurrent generation: Supramolecularly and covalently functionalized single-wall carbon nanotubes-polymer/porphyrin donor-acceptor nanohybrids - Rahman, Aminur; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Jux, Norbert; Tchoul, Maxim N.; Ford, Warren T.; Mateo-Alonso, Aurelio; Prato, Maurizio (Chemistry - A European Journal, 2008)
Novel nanohybrids based on covalently and noncovalently functionalized single-wall carbon nanotubes (SWNTs) have been prepared and assembled for the construction of photoactive electrodes. Polymer-grafted SWNTs were synthesized by free-radical polymerization of (vinylbenzyl)trimethylammonium chloride. Poly[(vinylbenzyl)trimethylammonium chloride] (PVBTA) was also noncovalently wrapped around SWNTs to form stable, positively charged SWNT/PVBTA suspensions in water. Versatile donor-acceptor nanohybrids were prepared by using the electrostatic/van der Waals interactions between covalent SWNT-PVBTA and/or noncovalent SWNT/PVBTA and porphyrins (HP and/or ZnP ). Several spectroscopic, microscopic, transient, and photoelectrochemical measurements were taken to characterize the resulting supramolecular complexes. Photoexcitation of the nanohybrids afforded long-lived radical ion pairs with lifetimes as long as 2.2 us. In the final part, photoactive electrodes were constructed by using a layer-by-layer technique on an indium tin oxide covered glass support. Photocurrent measurements gave remarkable internal photon-to-current efficiencies of 3.81 and 9.90% for the covalent ZnP-/SWNT-PVBTA and noncovalent ZnP /SWNT/PVBTA complex, respectively, when a potential of 0.5 V was applied. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Morphology analysis of near IR sensitized polymer/fullerene organic solar cells by implementing low bandgap heteroanalogue C-/Si-PCPDTBT - Ameri, Tayebeh; Khoram, Parisa; Heumüller, Thomas; Baran, Derya; Machui, Florian; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Halik, Marcus; Rathgeber, Silke; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
In the current work, we have investigated the morphological aspects of the ternary solar cells based on host matrices of P3HT:PCBM and P3HT:ICBA, using the low bandgap polymer analogues of C- and Si-bridged PCPDTBT as near IR sensitizers, which show noticeably different performance. A direct comparison of these well-functional and poorly functional ternary blend systems provides insights into the bottlenecks of device performance and enables us to set up an initial set of design rules for ternary organic solar cells. Our study reveals the importance of surface energy as a driving force controlling sensitizer location and morphology formation of ternary blends. The interfacial surface energy results indicate that Si-PCPDTBT locates at amorphous interfaces and P3HT crystallites, while C-PCPDTBT tends to accumulate at amorphous interfaces and semi-crystalline (or agglomerated) domains of the fullerene derivatives. GIWAXS and SCLC results support this prediction where adding high content of C-PCPDTBT influences mainly the semi-crystallinity (aggregation) of the fullerene and reduces the electron mobility, but Si-PCPDTBT impacts mainly the P3HT ordering and, in turn, deteriorates the hole mobility. These findings show that the disruption of the fullerene semi-crystalline domains is more detrimental to the device performance than the disruption of the polymer domains.

Multilayer assembly for solar energy conversion - Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael (Fullerenes and Other Carbon-Rich Nanostructures, 2014)
Organizing molecular thin films of electro- and photoactive building blocks provides a versatile platform to the nanoscale control of assembled multilayers and paves the way for the design of functional electronic devices and/or efficient photoenergy conversion devices. Assembly methods, including the Langmuir–Blodgett and the layer-by-layer technique, offer elegant means to realize well-ordered multifunctional thin films on variable surfaces. In this chapter, the fundamental factors and driving forces that govern the adsorption processes of multilayered assemblies are highlighted and numerous intriguing contributions to the field of template-assisted assemblies are presented. Owing to the applicability of these concepts to carbon-based materials – fullerenes and carbon nanotubes – particular attention is paid to the integration of these exceptionally materials combined with light absorbing constituents into nanostructured thin films en route towards versatile electron donor–acceptor nanohybrids for photoconversion schemes.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Carbon nanotubes; Fullerenes; Langmuir Blodgett; Langmuir Schaefer; Layer by layer; Self assembly; Solar cells

P-doped multiwall carbon nanotube/perylene diimide derivative photoelectrochemical cells for photocurrent generation - Troeger, Anna; Ledendecker, Marc; Margraf, Johannes; Sgobba, Vito; Guldi, Dirk Michael; Vieweg, Benito; Spiecker, Erdmann; Suraru, Sabin-Lucian; Wuerthner, Frank (Advanced Energy Materials, 2012)
A perylene diimide (PDI) derivative bearing four chlorine substituents in the bay area is deposited together with pristine multiwall carbon nanotubes (MWNTs) and/or Nafion p-doped MWNTs (p-MWNTs) onto indium tin oxide (ITO) solid substrates by means of air-brushing. The resulting photoanodes are studied in photoelectrochemical cells and reveal highest photocurrent efficiencies when PDI and p-MWNT are combined as photoactive materials, indicating the beneficial effect of Nafion.

Transient absorption spectroscopy studies on polythiophene-fullerene bulk heterojunction organic blend films sensitized with a low-bandgap polymer - Löslein, Heiko; Ameri, Tayebeh; Matt, Gebhard; Koppe, Markus; Egelhaaf, Hans J.; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Brabec, Christoph (Macromolecular Rapid Communications, 2013)
Recently, the concept of near-infrared sensitization is successfully employed to increase the light harvesting in large-bandgap polymer-based solar cells. To gain deeper insights into the operation mechanism of ternary organic solar cells, a comprehensive understanding of charge transfer-charge transport in ternary blends is a necessity. Herein, P3HT:PCPDTBT:PCBM ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the P3HT:PCPDTBT:PCBM 0.9:0.1:1 blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Polythiophene-fullerene bulk heterojunction ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Two similar near-infrared (IR) absorbing benzannulated AZA-bodipy dyes as near-ir sensitizers for ternary solar cells - Min, Jie; Ameri, Tayebeh; Gresser, Roland; Lorenz-Rothe, Melanie; Baran, Derya; Troeger, Anna; Sgobba, Vito; Leo, Karl; Riede, Moritz; Guldi, Dirk Michael; Brabec, Christoph (ACS Applied Materials and Interfaces, 2013)
Ternary composite inverted organic solar cells based on poly(3-hexylthiophen-2,5-diyl) (P3HT) and phenyl-C-butyric acid methyl ester (PCBM) blended with two different near-infrared absorbing benzannulated aza-BODIPY dyes, difluoro-bora-bis-(1-phenyl-indoyl)-azamethine (1) or difluoro-bora-bis-(1-(5-methylthiophen)-indoyl)-azamethine (2), were constructed and characterized. The amount of these two aza-BODIPY dyes, within the P3HT and PCBM matrix, was systematically varied, and the characteristics of the respective devices were recorded. Although the addition of both aza-BODIPY dyes enhanced the absorption of the blends, only the addition of 1 improved the overall power conversion efficiency (PCE) in the near-infrared (IR) region. The present work paves the way for the integration of near-infrared absorbing aza-BODIPY derivatives as sensitizers in ternary composite solar cells. © 2013 American Chemical Society.